Awareness And Perception of Manual Therapy In Improving Woment's Fertility Among Physiotherapists In Malaysia: A Cross-Sectional Study - Shirley, C.L; Yughdtheswari, Muniandy; Sharmila, G.K.P; Siti Hazirah, S. (INTI International University, 2020)
Problem Statement: Infertility is a global health care concern and is clinically defined as failure to attain clinical pregnancy despite 12 months or more unprotected coitus. Manual therapy (MT), commonly used in physiotherapy, is used as part of infertility management. To date, no research concerning MT in infertility management in Malaysia.